Management of Regular BOS Fund for the Procurement of Multimedia Learning Tools - Sodiq, Akhmad; Egar, Ngasbun; Nugroho, Aryo Andri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
his study aims to analyze the management of Regular School Operational Assistance (BOS) funds in the procurement of multimedia learning tools at SD Negeri 1 Donosari, Patebon District, Kendal Regency. This research employed a qualitative approach with a case study design to gain an in-depth understanding of school financial management practices. Data were collected through in-depth interviews, observations, and documentation involving the principal, BOS treasurer, and several teachers directly involved in the management and utilization of BOS funds. The interviews focused on planning, implementation, and reporting processes of Regular BOS funds, while observations and documentation were used to examine financial administration practices, RKAS documents, financial reports, and availability of multimedia learning tools. The data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that BOS fund management has been implemented effectively through three main stages: planning and budgeting are conducted through the preparation of the School Activity and Budget Plan (RKAS) based on school needs and stakeholder involvement; implementation is carried out systematically in accordance with technical guidelines and supported by proper financial administration; and reporting and accountability are performed transparently and periodically to ensure compliance with regulations. The success of this management is supported by appropriate budget prioritization, a strong internal control system, and optimal utilization of available resources. In conclusion, effective and accountable management of BOS funds contributes significantly to the availability of multimedia learning tools and enhances the quality of the teaching and learning process in schools.